The Synergy of Moderate Islam and Curriculum Reform in Character Education - Masripah; Mohammad, Yufi (Yayasan Sinergi Kawula Muda, 2025)
This study explores the integration of moderate values in character education through a narrative review of current literature, with a specific focus on Islamic educational settings such as madrasahs. The aim is to understand how character formation can be effectively achieved through a synthesis of religious traditions and modern pedagogical innovations. The review adopts a narrative method to critically examine key thematic patterns, drawing from empirical studies and qualitative insights. Results reveal that integrating moderate religious values with educational curricula enhances moral development, social tolerance, and holistic student character. Educators play a crucial role, particularly through narrative teaching methods and curriculum innovations that align with cultural contexts. Systemic factors such as rigid policies, bureaucratic institutional structures, and social disparities are identified as major challenges. The discussion advocates for reformative actions, including decentralizing education policy, improving teacher training, and incorporating digital and project-based learning. This review enriches existing academic discourse by emphasizing narrative and emotional engagement, providing a holistic framework for educational reform. The study concludes that character education must be dynamic, culturally adaptive, and grounded in moderate values to effectively respond to contemporary global and local educational demands.